Inclusão e acessibilidade: um estudo sobre o acesso e a permanência de estudantes com deficiência da Universidade Federal do Rio Grande do Sul - Riella, Michele da Silva Nimeth (Universidade do Vale do Rio dos Sinos, 2020)
This research investigates mainly the Federal University of Rio Grande do Sul (UFRGS)‟ access and permanence conditions, in relation to the perspective of students with disabilities. The main objective of this study is to analyze both the perception and the satisfaction degree of the students, in relation to the accessibility of the University, seeking to identify needs and / or demands, for inclusive education, in order to contribute and to qualify University‟s educational management. The following strategies were used to obtain the results: bibliographic and documental analysis and exploratory research. The bibliographic research presents the relevant legal frameworks, regarding the inclusion process of people with disabilities, and the theoretical concepts, which include inclusive education, in the context of Brazilian higher education system, with a focus on the expansion policies of public universities, which permeate both public and educational policies of inclusion, in Brazil and other countries, as well as the situation of people with disabilities in higher education system and the current situation of the educational system in public universities; the documentary research addresses, through public documents, UFRGS‟ inclusive actions, in addition to presenting the position of Brazilian Ministry of Education (MEC) and the data of the Brazilian National Studies and Research Institute (INEP), in relation to the theme; in exploratory research, it was used a ten-question script semi-structured interview, which included the participation of six students. The questions address the following aspects: the admission process, services, interpersonal, social and academic relationships, the learning process and both academic and professional education. The data were analyzed qualitatively, by using the content analysis technique as a methodology. Based on the research, major advances and progress were identified, regarding to both legal provisions and implementation of inclusive public policies on higher education, reflecting an evolution in the conception and understanding of the theme, expanding the discussion on this aspect and providing an increase in the number of students with disabilities in these institutions in recent years, albeit minor and incipient. It was identified an increment, at UFRGS, in relation to inclusive actions, through the adoption of services and assistance directed to accessibility issues, especially from the creation of the Inclusion and Accessibility Center (Incluir). However, from the interviewee‟s point of view, there is still much to do, considering all the difficulties that these students encounter, during their academic trajectories, concerning the aspects of this study. Furthermore, architectural, urban and attitudinal barriers were the most cited by the participants, being predominant in this context. At the same time, it was possible to perceive 10 the development of strategies, empowerment and leadership, by these students. Therefore, the study contemplates an arsenal of questions, problematizations, suggestions and new perceptions, arising from these students, making it possible to rethink both inclusion and accessibility conditions at the University, in order to establish possible strategies and changes, contributing to institutional and social development.
Keywords: Acessibilidade; Inclusão; Universidade; Estudantes com deficiência; Permanência; Accessibility; Inclusion; University; Students with disabilities; Permanence; ACCNPQ::Ciências Humanas::Educação